CONTRIBUTION OF CAMPUS TEACHING PROGRAMS IN IMPROVING THE STUDENTS’ NUMERACY LITERACY COMPETENCE IN PARTNER SCHOOL - Acep Musliman; Fitri Damayanti (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
The research in this paper was conducted on Campus Teaching 5 (KM5) activities as a form of the Independent Learning–Independent Campus (Merdeka Belajar–Kampus Merdeka/MBKM) program in partner schools. It aims to provide opportunities for students to carry out activities outside the lecture classroom as a self-development experience. This research seeks to determine the effectiveness of improving literacy, numeracy, and students’ character as a result of the transformation carried out by students through campus teaching activities toward improving the quality of learning services in partner schools. The expected transformation is an increase in literacy, numeracy, and students’ character competencies through an innovative, creative, and enjoyable learning process. The research employed mixed methods, combining quantitative and qualitative descriptive approaches. Research data were obtained from weekly reports of students’ activities at the assisted partner school, namely Perti Islamic Private Elementary School in West Jakarta. The data consisted of two types: qualitative data from weekly reports and quantitative data derived from the results of the Minimum Competency Assessment (AKM) pretest and posttest. Based on the qualitative data analysis of weekly reports, the transformation process had an impact on improvements in literacy, numeracy, and students’ character competencies. This is also supported by the AKM results, which show a positive difference in the mean scores between the pretest and posttest. This indicates an improvement in literacy, numeracy, and students’ character competencies. Therefore, it can be concluded that the Campus Teaching program is effective in improving students’ literacy, numeracy, and character competencies.